THE ROLE OF THE VILLAGE COMMUNITY AS A FORM OF LOCAL WISDOM IN REALIZING ANTI-CORRUPTION CULTURE: A STRATEGY TO ERADICATE CORRUPTION IN THE VILLAGE - Agus Surono (Association of Certified Fraud Examiners Indonesia Chapter, 2018)
No. 6 of 2014 on the Village has given a new hope for Indonesia, because the village is expected to increase the country’s economy through the management of natural resources on a village scale, including in the use of village funds for the welfare of the community. In the provisions of the Village Law, the village has the following authorities: authority based on the right of origin, local authority on village scale, authority in accordance with the duties of the government such as provincial government or district/city government, and other authorities assigned by the Government, Province. In addition to these opportunities, enactment of the Village Law also gives the village the rights to manage its funding resources in the form of village funds that can be used by villagers to support various village activities according to the potential in each village. However, in the implementation of the management of the village funds, there will always be irregularities done by village heads, village officials or local government officials who have authority in disbursing the village funds. Even sometimes there are corrupt practices in the use of the village funds. Paragraph 12 of the explanation of Law No. 31 of 1999 mentions that community can participate in the prevention and eradication of corruption and the members of the community who have participated are given legal protection and appreciation. One step in preventing corruption is done by growing anti-corruption culture through strengthening the role of rural community in improving anti-corruption culture in the village. The role of the village community is very important, as a form of local wisdom, to prevent corruption in the village.